Marriage Experience from the Girl’s Perspective: A Scoping Review - Farhah Kamilah; Elyse Maria Rosa (Universitas Airlangga, 2021)
Background: Child marriage is a marriage that is conducted formally or informally by spouses or with one of the spouses aged 18. Child marriage is a phenomenon that involves socio-cultural elements thus many factors influence it. Girls are 3 times more likely to experience child marriage than boys. Various conditions that occur in child marriage have generated interest in seeing a broader view of how married girls view their married life. Objective: This review was conducted to explore research findings related to the experiences of girls who were married under 18 years of age so that it could be used as an illustration to see the condition of girls in child marriage life. Methods: This review used three databases PubMed, ProQuest, and EbscoHost. The search for articles used main keywords, namely